Anti-PD-1 increases the clonality and activity of tumor infiltrating antigen specific T cells induced by a potent immune therapy consisting of vaccine and metronomic cyclophosphamide. Issue 1 (December 2016) - Weir, Genevieve; Hrytsenko, Olga; Quinton, Tara; Berinstein, Neil; Stanford, Marianne; Mansour, Marc
Abstract Background Future cancer immunotherapies will combine multiple treatments to generate functional immune responses to cancer antigens through synergistic, multi-modal mechanisms. In this study we explored the combination of three distinct immunotherapies: a class I restricted peptide-based cancer vaccine, metronomic cyclophosphamide (mCPA) and anti-PD-1 treatment in a murine tumor model expressing HPV16 E7 (C3). Methods Mice were implanted with C3 tumors subcutaneously. Tumor bearing mice were treated with mCPA (20 mg/kg/day PO) for seven continuous days on alternating weeks, vaccinated with HPV16 E749-57 peptide antigen formulated in the DepoVax (DPX) adjuvanting platform every second week, and administered anti-PD-1 (200 μg/dose IP) after each vaccination. Efficacy was measured by following tumor growth and survival. Immunogenicity was measured by IFN-γ ELISpot of spleen, vaccine draining lymph nodes and tumor draining lymph nodes. Tumor infiltration was measured by flow cytometry for CD8α+ peptide-specific T cells and RT-qPCR for cytotoxic proteins. The clonality of tumor infiltrating T cells was measured by TCRβ sequencing using genomic DNA. Results Untreated C3 tumors had low expression of PD-L1 in vivo and anti-PD-1 therapy alone provided no protection from tumor growth. Treatment with DPX/mCPA could delay tumor growth, and tri-therapy with DPX/mCPA/anti-PD-1 provided long-term control of tumors. We found that treatment with DPX/mCPA/anti-PD-1 enhanced systemic antigen-specific immune responses detected in the spleen as determined by IFN-γ ELISpot compared to those in the DPX/mCPA group, but immune responses in tumor-draining lymph nodes were not increased. Although no increases in antigen-specific CD8α+ TILs could be detected, there was a trend for increased expression of cytotoxic genes within the tumor microenvironment as well as an increase in clonality in mice treated with DPX/mCPA/anti-PD-1 compared to those with anti-PD-1 alone or DPX/mCPA. Using a library of antigen-specific CD8α+ T cell clones, we found that antigen-specific clones were more frequently expanded in the DPX/mCPA/anti-PD-1 treated group. Conclusions These results demonstrate how the efficacy of anti-PD-1 may be improved by combination with a potent and targeted T cell activating immune therapy.